Türkiye TVBB potansiyeli - Saraç, Selim; Baykaş, Tuncer (Institute of Electrical and Electronics Engineers Inc., 2016)
Kablosuz haberleşme teknolojilerinin gelişmesiylemevcut frekans spektrumunun kullanımına ait talepler deartmaktadır. Dinamik spektrum erişimi (DSA) bu talebinkarşılanması için çözüm olabilecek bir kavramdır. Bukavram lisanslı kablosuz haberleşme sistemlerininkullanmadığı frekans bantlarının bulunması ve kullanımasunulması amacını da içerir. 2000’li yılların başındanitibaren öncelikle Amerika daha sonra Birleşik Krallık vedaha sonra Avrupa’da ortaya çıkan; TV Beyaz Boşluk,karasal TV frekans yayını bantlarının ikincil amaçlar içinkullanılmasına olanak tanıyan bir teknolojidir. Bu makaledeTVBB (TV Beyaz Boşluk) için Türkiye’deki mevcut durum, yapılabilirliği, teknik altyapısı ve uygulama alanları incelenecektir.

Demand on the existent frequency spectrum increases by the development of the wireless communication technologies. Dynamic Spectrum Access (DSA) is a concept that should be a solution for this demand. This concept consists of to find and serve into use the frequency bands that licensed wireless communication systems don't use as a purpose also. From the beginning of 2000's, primarily in US later in UK and after in Europe, TVWS is a technology that can give opportunity to use terrestrial TV broadcasting frequencies as a secondary purposes. In this paper the current status in Turkey, feasibility, technical infrastructure and usage areas will be investigated.
TVWS potential in Turkey
Keywords: TVBB; Frekans Planlaması; İnternet Yayını; TVWS; Frequency Planning; Internet Broadcasting